Intra-night variability of the blazar CTA 102 during its 2012 and 2016 giant outbursts. Issue 2 (19th July 2017) - Bachev, R.; Popov, V.; Strigachev, A.; Semkov, E.; Ibryamov, S.; Spassov, B.; Latev, G.; Muñoz Dimitrova, R. V.; Boeva, S.
Abstract: We obtained and analysed more than 100 h of multicolour optical time series of the blazar CTA 102 during its 2012 and 2016 outbursts. The object reached almost 11th mag at the end of 2016, which is perhaps the brightest blazar state ever observed! During both outbursts, CTA 102 showed significant and rapid variability on intra-night time-scales, reaching up to 0.2 mag for 30 min on some occasions. The 'rms-flux' relation, built for all data sets, shows a large scatter and no apparent saturation on the magnitude scale. The ensemble structure function of the light curves can be fitted well with a straight line of a slope of ∼0.4. The time lags between the different optical bands appear to be consistent with zero, taking into account our time resolution. We discuss different variability scenarios and favour the changing Doppler factor of the emitting blobs as the most plausible one to account for the observed intra-night variability.